ChemInform Abstract: Palladium‐Catalyzed Regioselective [3 + 2] Annulation of Internal Alkynes and Iodopyranoquinolines with Concomitant Ring Opening. Issue 9 (5th March 2013) - Aggarwal, Trapti; Jha, Rajeev R.; Tiwari, Rakesh K.; Kumar, Sonu; Kotla, Siva K. Reddy; Kumar, Sushil; Verma, Akhilesh K.
Abstract Unsymmetrical internal alkynes such as (X) or (XII) generate selectively a single isomers [cf.(XI) or (XIII)].